Deciphering the molecular mechanism of FLT3 resistance mutations - Georgoulia, Panagiota S.; Bjelic, Sinisa; Friedman, Ran (The FEBS journal, 2020)
FMS‐like tyrosine kinase 3 (FLT3) has been found to be mutated in ~ 30% of acute myeloid leukaemia patients. Small‐molecule inhibitors targeting FLT3 that are currently approved or still undergoing clinical trials are subject to drug resistance due to FLT3 mutations. How these mutations lead to drug resistance is hitherto poorly understood. Herein, we studied the molecular mechanism of the drug resistance mutations D835N, Y842S and M664I, which confer resistance against the most advanced inhibitors, quizartinib and PLX3397 (pexidartinib), using enzyme kinetics and computer simulations. In vitro kinase assays were performed to measure the comparative catalytic activity of the native protein and the mutants, using a bacterial expression system developed to this aim. Our results reveal that the differential drug sensitivity profiles can be rationalised by the dynamics of the protein–drug interactions and perturbation of the intraprotein contacts upon mutations. Drug binding induced a single conformation in the native protein, whereas multiple conformations were observed otherwise (in the mutants or in the absence of drugs). The end‐point kinetics measurements indicated that the three resistant mutants conferred catalytic activity that is at least as high as that of the reference without such mutations. Overall, our calculations and measurements suggest that the structural dynamics of the drug‐resistant mutants that affect the active state and the increased conformational freedom of the remaining inactive drug‐bound population are the two major factors that contribute to drug resistance in FLT3 harbouring cancer cells. Our results explain the mechanism of drug resistance mutations and can aid to the design of more effective tyrosine kinase inhibitors. FMS‐like tyrosine kinase 3 (FLT3) is a kinase that is an important drug target in leukaemias, but resistance to therapies directed at FLT3 occurs often due to mutations. We used enzymatic experiments and computer simulations to study how mutations lead to resistance, and found that the main effect is increased activity, which is explained by structural and dynamic changes to the active conformation.